New Ba0.5Sr0.5Co0.8Fe0.2O 3-d + Co3O4 composite electrode for IT-SOFCs with improved electrical conductivity and catalytic activity - Chen, D.; Huang, C.; Ran, R.; Park, H.; Kwak, C.; Shao, Zongping (2011)
Ba0.5Sr0.5Co0.8Fe0.2O 3-d (BSCF) + Co3O4 composites with different Co3O4 contents were synthesized, and their properties and performance as cathodes in IT-SOFCs were investigated. The diffraction patterns of the composites were well indexed based on the physical mixture of the BSCF phase and the Co3O4 phase. A surprising increase in the total conductivity of the composites was observed even though Co3O4 is a p-type semiconductor with a low conductivity. Electrochemical impedance spectra of symmetric cells indicated that both the area specific resistance and the activation energy were reduced in samples with Co3O4 contents of 5-20 wt.% with minimum values reaching 10 wt.%. A synergistic effect likely occurred between BSCF and Co3O4 that led to the better performance. An anode-supported single cell with 90 wt.% BSCF + 10 wt.% Co3O 4 delivered a promising peak power density of 1150 mW cm - 2 at 600 °C. © 2011 Elsevier B.V.